Anxiety comorbidities in patients with major depressive disorder: the role of attachment. (2nd October 2019) - Huang, Yu-Chi; Lee, Yu; Lin, Pao-Yen; Hung, Chi-Fa; Lee, Chun-Yi; Wang, Liang-Jen
Abstract: Objectives: Attachment connects mood expressions and is related to the psychopathology of depression and anxiety. However, whether insecure attachment can predict the risk of an increased number of anxiety comorbidities in patients with major depressive disorder (MDD) remains unclear. Methods: Sixty-six patients with MDD were recruited in this cross-sectional study. Depression, anxiety and insecure attachment among patients were assessed accordingly. Patients' disease characteristics and psychopathology were evaluated using a structured psychiatric MINI interview, the 17-item Hamilton Depression Rating Scale, and the 21-item Beck Anxiety Inventory, while the attachment was assessed with the Chinese self-reporting version of the Attachment Style Questionnaire. Results: We found that 74.2% of MDD patients had at least one anxiety comorbidity, and 24.2% of MDD patients had multiple anxiety comorbidities. Common anxiety comorbidities included generalised anxiety disorder, panic disorder, agoraphobia, and post-traumatic stress disorder. The patients who had multiple anxiety comorbidities exhibited lower secure attachment levels and higher anxious/preoccupied and avoidant attachment levels. Conclusions: Anxious/preoccupied attachment is associated with an increased risk of multiple anxiety comorbidities in MDD patients. A longitudinal study with a larger sample size is needed to identify the causal relationship of anxious/preoccupied attachment and anxiety comorbidities during the course of MDD.